Strengthening Integrated Mental Health Services: Implementation of Community Mental Health Wellness Centre in Langsat, Pekanbaru - Yunita, Jasrida; Ismainar, Hetty; Niriyah, Sekani; Anwir, Harvandy; Fauziah, Kharisma Yuhana; Wahyuni, Anggi; Nurlisis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Integrated Mental Health Services at Langsat Public Health Centre were implemented to address low community awareness of mental health screening, stigma toward individuals with mental disorders or mental health problems, and limited educational and support facilities. This program aimed to enhance the capacity of primary health care staff and community health cadres, strengthen the reporting and service management system, and promote community participation through mental health promotion and screening by establishing the Community Mental Health Wellness Centre. The methods included collaborative discussions, training for health workers and cadres, development of Standard Operating Procedures (SOPs) and service guidelines, and production of educational media and promotional videos. An integrated reporting system using e-Puskesmas and Google Spreadsheets enabled real-time data monitoring. The results included the development of SOPs and an Integrated Mental Health Service Guideline as official references, improved understanding among health workers and cadres regarding service flow, counseling, patient support, and reporting mechanisms, and the availability of educational media disseminated through social media and primary health care waiting areas. The program produced SOPs, service guidelines, educational media (posters and leaflets), and established the Community Mental Health Wellness Centre as a replicable model that strengthens community-based mental health services and enhances community engagement.